HBV coinfection is associated with reduced CD4 response to antiretroviral treatment in pregnancy. Issue 2 (4th March 2017) - Floridia, Marco; Masuelli, Giulia; Tamburrini, Enrica; Spinillo, Arsenio; Simonazzi, Giuliana; Guaraldi, Giovanni; Degli Antoni, Anna Maria; Martinelli, Pasquale; Portelli, Vincenzo; Dalzero, Serena; Ravizza, Marina
Abstract : Objective: To evaluate the impact of Hepatitis B virus (HBV) coinfection on response to antiretroviral treatment in pregnant women with HIV. Methods: Retrospective analysis of a large case series of pregnant women with HIV in Italy; outcome measures were CD4 changes, HIV viral load, and main pregnancy outcomes (preterm delivery, low birthweight, intrauterine growth restriction, mode of delivery, and major birth defects). Results: Rate of HBV coinfection among 1462 pregnancies was 12.0%. Compared to the HBV-uninfected, HBV-coinfected women had a significantly lower median CD4 cell gain between first and third trimester (26.5 vs. 60 cells/mm 3, p  = 0.034), with similar rate of undetectable (<50 copies/ml) HIV-RNA at third trimester (70.5% vs. 65.2%, p  = 0.229), and no differences in all the main maternal and infant outcomes. A multivariable linear regression analysis identified four variables significantly and independently associated with a lower CD4 response in pregnancy: HBV coinfection (–35 cells/mm 3 ), being on antiretroviral treatment at conception (–59.7 cells/mm 3 ), AIDS status (–59.8 cells/mm 3 ) and higher first CD4 levels in pregnancy (–0.24 cells per unitary CD4 increase). Conclusions: HBV coinfection had no adverse influence on the main pregnancy outcomes or on HIV viral load suppression in late pregnancy but was associated with a significantly reduced CD4 response in pregnancy. This effect might have clinical relevance, particularly in women with advanced immune deterioration.